RANCANG BANGUN SISTEM INFORMASI CAPABILITY ASSESSMENT TOOLS COBIT 2019 - Sherina Salsabila Mandiangan (2023)
As time progresses, digitalized companies increasingly depend on I&T for their survival and growth. Stakeholder value creation is often driven by high levels of digitalization in new business models, efficient processes, successful innovation, etc. And for more than 25 years, COBIT has built and integrated a framework of practices aimed at helping the I&T governance process so that the process can understand, design and implement Enterprise Governance of Information and Technology (EGIT). PT. Lifelong Learning Multimatics as an IT Training and Consulting Company which has been operating for almost 20 years in providing IT training and consulting services also uses COBIT 2019 as a reference in assessing the IT Maturity Level in Client Companies. However, in its implementation, the assessment is still carried out manually using Microsoft Excel as the application facility which is considered to still have several shortcomings such as waste of memory for one file with many sheets, the possibility of redundant data, the selection of subdomain processes which still have to be deleted manually, and difficulties in making reports. This research uses the Agile Scrum method which will produce an Information System that can be used to facilitate consultants in carrying out Capability Assessments on the COBIT 2019 framework. This research produces a website-based Information System which is used as a tool for assessing a company's IT Maturity Level using COBIT 2019.